(untitled) (Research, Society and Development, 2023)
Introduction: Cholelithiasis are stones that form in the gallbladder. Its main symptom is biliary colic with pain in the right hypochondrium, which may be accompanied by nausea and vomiting. This condition affects about 10-20% of the general population. Objective: To approach the use of imaging methods for diagnosing cholelithiasis, focusing on computed tomography. Methodology: An integrative literature review was performed by searching for scientific publications indexed in the following databases: SciELO, Portal BVS and PubMed. The following descriptors were used: (cholelithiasis) AND (diagnosis). 20 publications were selected as a sample for this article. Discussion: Abdominal and biliary ultrasonography (USG) is the most appropriate imaging method in cases of suspected cholelithiasis, as it presents high sensitivity and specificity for identifying gallbladder stones. Computed tomography (CT) is the imaging method indicated to exclude differential diagnoses and to evaluate the evolution of the condition and its complications. Conclusion: CT is not the imaging exam of choice for such diagnosis, due to its cost price, execution time and result, besides not having high sensitivity and specificity for the confirmation of cholelithiasis diagnosis.